A new perspective on the role of the CREB family of transcription factors in memory consolidation via adult hippocampal neurogenesis - Ortega-Martínez, Sylvia (Frontiers in Molecular Neuroscience, 2015)
Adult neurogenesis is the process by which new neurons are generated in the brains of adults. Since its discovery 50 years ago, adult neurogenesis has been widely studied in the mammalian brain and has provided a new perspective on the pathophysiology of many psychiatric and neurodegenerative disorders, some of which affect memory. In this regard, adult hippocampal neurogenesis (AHN), which occurs in the subgranular zone of the dentate gyrus, has been suggested to play a role in the formation and consolidation of new memories. This process involves many transcription factors, of which cyclic AMP-responsive element-binding protein (CREB) is a well-documented one. In the developing brain, CREB regulates crucial cell stages, (e.g., proliferation, differentiation, and survival), and in the adult brain, it participates in neuronal plasticity, learning, and memory. In addition, new evidence supports the hypothesis that CREB may also participate in learning and memory through its involvement in AHN. This review examines the CREB family of transcription factors, including the different members and known signaling pathways. It highlights the role of CREB as a modulator of AHN, which could underlie its function in memory consolidation mechanisms.